Perioperative intravenous contrast administration and the incidence of acute kidney injury after major gastrointestinal surgery: prospective, multicentre cohort study. Issue 8 (5th February 2020) - ,
Abstract : Background: This study aimed to determine the impact of preoperative exposure to intravenous contrast for CT and the risk of developing postoperative acute kidney injury (AKI) in patients undergoing major gastrointestinal surgery. Methods: This prospective, multicentre cohort study included adults undergoing gastrointestinal resection, stoma reversal or liver resection. Both elective and emergency procedures were included. Preoperative exposure to intravenous contrast was defined as exposure to contrast administered for the purposes of CT up to 7 days before surgery. The primary endpoint was the rate of AKI within 7 days. Propensity score‐matched models were adjusted for patient, disease and operative variables. In a sensitivity analysis, a propensity score‐matched model explored the association between preoperative exposure to contrast and AKI in the first 48 h after surgery. Results: A total of 5378 patients were included across 173 centres. Overall, 1249 patients (23·2 per cent) received intravenous contrast. The overall rate of AKI within 7 days of surgery was 13·4 per cent (718 of 5378). In the propensity score‐matched model, preoperative exposure to contrast was not associated with AKI within 7 days (odds ratio (OR) 0·95, 95 per cent c.i. 0·73 to 1·21;  P  = 0·669). The sensitivity analysis showed no association between preoperative contrast administration and AKI within 48 h after operation (OR 1·09, 0·84 to 1·41; P  = 0·498). Conclusion: There was no association between preoperative intravenous contrast administered for CT up to 7 days before surgery and postoperative AKI. Risk of contrast‐induced nephropathy should not be used as a reason to avoid contrast‐enhanced CT. Abstract : This secondary analysis of the Outcomes After Kidney injury in Surgery (OAKS) data set aimed to determine the impact of perioperative exposure to intravenous contrast for CT and the risk of developing postoperative acute kidney injury (AKI) in patients undergoing major gastrointestinal surgery. There was no association between preoperative or postoperative intravenous contrast administered for CT up to 7 days before surgery and postoperative AKI. No effect on acute kidney injury Abstract : Antecedentes: El objetivo de este estudio fue determinar el impacto de la exposición preoperatoria al contraste intravenoso para la tomografía computarizada (TC) y el riesgo de desarrollar insuficiencia renal aguda (IRA) postoperatoria en pacientes sometidos a cirugía gastrointestinal mayor. Métodos: Este estudio de cohorte prospectivo y multicéntrico incluyó adultos sometidos a una resección gastrointestinal, cierre de estoma o resección hepática. Se incluyeron tanto procedimientos electivos como urgentes. La exposición al contraste intravenoso preoperatorio se definió como la administración de contraste para la realización de una TC durante los 7 días previos a la cirugía. El criterio de valoración principal fue la tasa de IRA a los 7 días. Se utilizaron modelos de puntuación de propensión emparejados ( propensity score matched, PSM) ajustados por paciente, enfermedad y variables operatorias. Los resultados del modelo se presentan como razón de oportunidades ( odds ratio, OR) e i.c. del 95%. En un análisis de sensibilidad, se examinó la asociación entre la exposición preoperatoria al contraste y la IRA en las primeras 48 horas después de la cirugía mediante un modelo de PSM. Resultados: Se incluyeron un total de 5.378 pacientes de 173 centros. Globalmente, el 23, 2% ( n = 1.249) de los pacientes recibieron medios de contraste intravenosos. La tasa global de IRA postoperatoria a los 7 días fue del 13, 4% (718/5.378). En el modelo de puntuación de propensión emparejado, la exposición preoperatoria al contraste no se asoció con IRA a los 7 días (OR 0, 95; i.c. del 95%: 0, 73‐1, 21; P = 0, 669). En el análisis de sensibilidad no se observó una asociación entre la administración de contraste preoperatorio y la IRA postoperatoria a las 48 horas (OR 1, 09; i.c. del 95% 0, 84‐1, 41; P = 0, 498). Conclusión: No hubo asociación entre la administración preoperatoria de contraste intravenoso para tomografías computarizadas durante los 7 días previos a la cirugía y la IRA postoperatoria. El riesgo de nefropatía inducida por el contraste no debe usarse de manera rutinaria como una razón para evitar la práctica de un TC con contraste.